HLA tapasin independence: broader peptide repertoire and HIV control. - Bashirova, Arman A.; Viard, Mathias; Naranbhai, Vivek; Grifoni, Alba; Garcia-Beltran, Wilfredo; Akdag, Marjan; Yuki, Yuko; Gao, Xiaojiang; O’hUigin, Colm; Raghavan, Malini; Wolinsky, Steven; Bream, Jay H.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Human leukocyte antigen (HLA) class I allotypes vary in their ability to present peptides in the absence of tapasin, an essential component of the peptide loading complex. We quantified tapasin dependence of all allotypes that are common in European and African Americans (n = 97), which revealed a broad continuum of values. Ex vivo examination of cytotoxic T cell responses to the entire HIV-1 proteome from infected subjects indicates that tapasin-dependent allotypes present a more limited set of distinct peptides than do tapasin-independent allotypes, data supported by computational predictions. This suggests that variation in tapasin dependence may impact the strength of the immune responses by altering peptide repertoire size. In support of this model, we observed that individuals carrying HLA class I genotypes characterized by greater tapasin independence progress more slowly to AIDS and maintain lower viral loads, presumably due to increased breadth of peptide presentation. Thus, tapasin dependence level, like HLA zygosity, may serve as a means to restrict or expand breadth of the HLA-I peptide repertoire across humans, ultimately influencing immune responses to pathogens and vaccines.